Students’ Perceptions of the Effectiveness and Challenges of Online EFL Assessment in Libya during the Covid-19 Pandemic - Eman Fathia Baresh (LETS: Journal of Linguistics and English Teaching Studies, 2022)
Online platforms have been embraced in the teaching and learning of English as a second and foreign language in almost every country in the world.  Many studies have found out that the online medium is effective in the ESL/EFL teaching and learning. However, the area or assessment is still a challenge to many teachers and students in ESL/EFL teaching and learning. Therefore, this study investigates the Libyan undergraduates’ perceptions of online assessment. A survey research design is adopted for the study. Data were collected from 105 Libyan undergraduates from six universities using a questionnaire. The data were analysed using descriptive statistical analysis. The findings reveal that the students have positive perceptions towards online assessment because it is convenient, flexible and give instant feedback. In addition, the findings show that the online assessment motivates them to learn subject matter. They prefer the online assessment than the traditional assessment because online assessment is suitable for all subjects and students respectively. It enhances technical skills as well as self-learning skills. Many Libyan undergraduates are motivated and aware of the benefit of online assessment. On the other hand, the findings indicate that the students perceive online assessment to facilitate cheating among students.